An oinochoe from Incoronata. Apprenticeship and sperimentation in the West (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
This study concerns an oinochoe from trench D at Incoronata di Metaponto (Unimi excavations 1975-1976). The object is analyzed in the context of the first contacts between Greeks and indigenous people in Southern Italy, particularly open to experimentation and hybridity. The treatment of the decorative motif on the neck of the vase offers the opportunity to reflect on apprenticeship and transmission of craft knowledge in the Greek world.
Keywords: Incoronata; Magna Graecia; pottery; apprenticeship; hybridity; knowledge transmission; sperimentation